2015
DOI: 10.5858/arpa.2013-0667-oa
|View full text |Cite
|
Sign up to set email alerts
|

The Pulmonary Histopathology of Anti-KS Transfer RNA Synthetase Syndrome

Abstract: Context The clinical spectrum of the antisynthetase syndromes (AS) has been poorly defined, although some frequently present with pulmonary manifestations. The anti-KS anti–asparaginyl-transfer RNA synthetase syndrome is one in which pulmonary interstitial lung disease is almost always present and yet the histopathologic spectrum is not well described. Objective To define the morphologic manifestations of pulmonary disease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Antibodies against cN1A were described in IBM, PM/DM, Ssc, SLE, and Sjögren's syndrome (range 0-37%). However, associations with ILD have not been identified [26,27,[30][31][32]43,45]. We demonstrated novel data regarding the presence of cN1A antibodies in ILDs, including ASS, HP, and IPF.…”
Section: Discussionmentioning
confidence: 83%
“…Antibodies against cN1A were described in IBM, PM/DM, Ssc, SLE, and Sjögren's syndrome (range 0-37%). However, associations with ILD have not been identified [26,27,[30][31][32]43,45]. We demonstrated novel data regarding the presence of cN1A antibodies in ILDs, including ASS, HP, and IPF.…”
Section: Discussionmentioning
confidence: 83%
“…In order to bypass the gnosologic conundrum it is tempting to consider the presence of these highly specific antibodies as definitory of an underlying CTD in subjects with ILD, even in the absence of other manifestations. This would be of particular interest in those patients with ARS antibodies who present with a pulmonary-dominant disease and an UIP-like radiographic pattern, as has been described ( 29 ). This situation can be visualized in 1 patient from our IPAF cohort with anti-Jo1 who underwent a diagnostic surgical lung biopsy.…”
Section: Discussionmentioning
confidence: 97%
“…Schneider et al 10 Four showed bibasilar reticular infiltrates with traction bronchiectasis and subpleural honeycomb change; one showed bibasilar patchy ground glass infiltrates with subpleural sparing.…”
Section: Nsipmentioning
confidence: 98%
“…4 Anti-KS autoantibodies presumably target asparaginyl-tRNA synthetase, and are found in part of a group of ASS seen in a few patients with IIMs. [5][6][7][8][9][10][11][12] Because of their rarity, there is very limited information available on the clinical presentation patterns and evolution of disease associated with anti-KS associated ASS or anti-KS syndrome. The aim of the present study was to review the published literature on anti-KS syndrome and summarize clinical features and prognosis.…”
Section: Introductionmentioning
confidence: 99%